Annual Incidence Rate of Visual Field Abnormalities Determined by Frequency Doubling Technology Perimetry - Tadashi Nakano; Takeshi Hayashi; Toru Nakagawa; Toru Honda; Satoshi Owada; Hitoshi Endo; Masayuki Tatemichi (Journal of Preventive Medicine And Care, 2016)
Purpose: To determine an appropriate time interval for conducting mass screening for glaucoma, it is important to gather information on the annual incidence rate. Thus, a retrospective cohort study was conducted to determine the annual incidence rate of visual field abnormalities (VFA) among a workplace cohort. Methods: In an initial visual field test using frequency doubling technology (FDT) perimetry conducted on 3443 employees (mean age 47.4 ± 8.9, men/women = 2967/476), no abnormalities were observed. Subjects were followed-up with annual perimetric testing for seven years, with VFA being determined using FDT test (FDT-VFA). Results: Using theKaplan–Meier method (log rank test, p < 0.001), cumulative FDT-VFA rates (SE) at seven years for subjects in their 30s, 40s, 50s, and 60s or older were found to be 3.0% (0.6), 4.2 % (0.6), 4.8 (0.8), and 11.3% (0.2), respectively. A linear fit to the Kaplan–Meier results yielded an annual incidence rate of 0.42%, 0.60%, 0.77%, and 1.60% for the 30s, 40s, 50s, and ≥60s age groups, respectively. Conclusion: Our data suggest that the annual incidence rate of VFA is <0.7% per year in subjects younger than 60 years of age; however, it increases to 1.6% per year in older subjects, thus suggesting that the monitoring frequency of glaucoma patients may need to be adjusted as a function of their age and be performed more frequently after the age of 60 years
Keywords: Glaucoma